2023
DOI: 10.1038/s41598-022-26610-3
|View full text |Cite|
|
Sign up to set email alerts
|

A dual-mode neurostimulation approach to enhance athletic performance outcome in experienced taekwondo practitioners

Abstract: Transcranial Direct Current Stimulation (tDCS) is a growing empirical approach to improve athletic performance. Some recent studies have investigated the effects of transcutaneous spinal direct current stimulation (tsDCS) on the motor performance such as reaction time. TDCS and tsDCS can lead to alteration of the spontaneous neural activity, and the membrane potentials of motor neurons in cerebral cortex and spinal interneurons, respectively. Given the paucity of experimental studies on the non-invasive brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 47 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Parallel with those studies and our data, Bocci et al (2014) showed that cathodal tsDCS improves motor unit recruitment by making motoneurons more responsive to synaptic activation. Recently, Kamali et al (2023) showed that cathodal tsDCS improved motor function potentially through the effect of tsDCS over the spinal interneurons.…”
Section: Discussionmentioning
confidence: 99%
“…Parallel with those studies and our data, Bocci et al (2014) showed that cathodal tsDCS improves motor unit recruitment by making motoneurons more responsive to synaptic activation. Recently, Kamali et al (2023) showed that cathodal tsDCS improved motor function potentially through the effect of tsDCS over the spinal interneurons.…”
Section: Discussionmentioning
confidence: 99%
“…Since glutamate activates both ionic and G-protein coupled receptors, which are responsible for a lasting increase in efficacy of synaptic transmission in the spinal cord [ 61 ] and in the brain [ 62 ] (i.e., long term potentiation (LTP)), the hypothesis was advanced that tsDCS might be used as an additional technique to enhance motor activity [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] and to facilitate motor and cognitive recovery in post-stroke populations [ 33 , 34 , 35 , 55 , 56 , 57 , 58 , 59 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors hypothesized that while tsDCS acted locally over the spinal circuits, rTMS probably promoted changes in the presynaptic inhibition of spinal motoneurons [ 47 ]. Interestingly, beneficial effects were found in athletic performance of experienced boxers and taekwondo practitioners also by combining anodal tDCS over the motor cortex with cathodal tsDCS over the thoracic region [ 51 , 54 ]. Indeed, the simultaneous stimulation of motor cortex and spinal cord significantly improved selective attention and reaction times, which, in turn, enhanced athletic performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations